Disengagement of impacted fetal head during caesarean section in advanced labour using C-snorkel device versus the conventional method: a randomised control trial. - Shahzarul Fazril; Aqmar Suraya; Nor Azlin Mohamed Ismail; Rahana Abdul Rahman; Nirmala Kampan; Muhammad A Jamil (Department of Surgery, UKM Medical Centre, 2014)
This pilot study was a randomized control trial conducted in the labour ward and operating theatre of Pusat Perubatan UKM, between May 2013 to September 2013. The trial included 34 women whom were in advance labour during caesarean section. The C-snorkel device was used to disengage an impacted fetal head during caesarean section. Maternal outcomes evaluated were blood loss, blood transfusion, duration of surgery, incidence of extended tears and post operative infection. The fetal outcomes evaluated were APGAR score at 1 and 5 minutes, umbilical cord pH, trauma to the fetus during delivery and admission to the neonatal intensive care unit.